Hepatitis C Virus RNA Is Commonly Detectable in Rectal and Nasal Fluids of Patients With High Viremia. (28th September 2019) - Chromy, David; Schmidt, Ralf; Mandorfer, Mattias; Lang, Gerold Felician; Bauer, David; Schwabl, Philipp; Popow-Kraupp, Theresia; Reiberger, Thomas; Mayer, Florian
Abstract: Background: Increasing numbers of hepatitis C virus (HCV) infections among men who have sex with men (MSM) are being observed in the Western world. The actual routes of HCV transmission during high-risk sex practices and associated drug use remain poorly understood. Methods: Forty-seven patients with HCV were prospectively enrolled. Rectal and nasal swabs were collected to quantify HCV-RNA levels within rectal and nasal fluids. Contamination by occult rectal bleeding was excluded by guaiac paper test. Risk behavior was assessed by standardized questionnaires. Results: Median age was 41.9 years, 89% were HIV positive (+) (42/47) and 85% (40/47) were male, 58% (23/40) of whom were MSM. Acute HCV infection was diagnosed in 32% (15/47), with all patients being HIV+MSM and 93% (14/15) having a documented history of sexually transmitted disease. Thirty-three (70%) patients had ≥1 HCV+ swab sample (HCV+SS; 48%, 22/46 rectal; 62%, 29/47 nasal), and contamination with blood was excluded in all patients. Individuals with HCV+SS had significantly higher serum HCV-RNA levels than patients with HCV-negative SS (6.28 [IQR, 0.85] log IU/mL vs 4.08 [2.45] log IU/mL; P < .001). Using ROC-curve analysis, serum HCV-RNA cutoffs for ruling in/out any HCV+SS were established at 6.02 log IU/mL and 4.02 log IU/mL, respectively. Conclusions: HCV-RNA is commonly detectable in rectal and nasal fluids of both HIV+ and HIV-negative HCV patients with high serum HCV-RNA, independently of the suspected route of HCV transmission. Accordingly, high-risk sex practices and sharing of nasal drug-sniffing "tools" might be important HCV transmission routes, especially in patients with high serum HCV-RNA. Abstract : Hepatitis C virus (HCV) RNA was commonly detectable in nasal and rectal fluids of HIV-positive and HIV-negative patients with hepatitis C, especially among those with high serum HCV-RNA levels. This has important implications for patients counseling and risk-reduction efforts.